2011
DOI: 10.1111/j.1532-7078.2010.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Toddler Emotion Regulation With Mothers and Fathers: Temporal Associations Between Negative Affect and Behavioral Strategies

Abstract: The present study investigated temporal associations between putative emotion regulation strategies and negative affect in 20-month-old toddlers. Toddlers’ parent-focused, self-distraction, and toy-focused strategies, as well as negative affect, were rated on a second-by-second basis during laboratory parent-toddler interactions. Longitudinal mixed-effects models were conducted to determine the degree to which behavioral strategy use predicts subsequent negative affect and negative affect predicts subsequent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 29 publications
5
57
0
Order By: Relevance
“…Similarly, infants who were rated as disorganized with fathers also showed relatively high levels of self-comforting during the reunion episode, especially as they got older. Although self-comforting has been found to be an effective strategy for regulating distress during infancy (Ekas et al, 2011; Stifter & Braungart-Rieker, 1995), a heightened level of self-comforting during contexts in which parents are emotionally available such as the reunion episode is curious. Self-stimulating or repetitive behavior such as rocking or hair-stroking during the reunion episode of the Strange Situation can reflect a disorganized attachment system (Main & Solomon, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, infants who were rated as disorganized with fathers also showed relatively high levels of self-comforting during the reunion episode, especially as they got older. Although self-comforting has been found to be an effective strategy for regulating distress during infancy (Ekas et al, 2011; Stifter & Braungart-Rieker, 1995), a heightened level of self-comforting during contexts in which parents are emotionally available such as the reunion episode is curious. Self-stimulating or repetitive behavior such as rocking or hair-stroking during the reunion episode of the Strange Situation can reflect a disorganized attachment system (Main & Solomon, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work stemming from these data include three publications examining attachment but not infant SFP responses (Lickenbrock, Braungart-Rieker, Ekas, Zentall, Oshio, & Planalp, in press; Planalp & Braungart-Rieker, 2013; and Zentall, Braungart-Rieker, Ekas, & Lickenbrock, 2012), one examining second-by-second associations between affective and behavioral responses within the SFP but not attachment (Ekas, Lickenbrock, & Braungart-Rieker, 2013), and two looking neither at attachment nor infant SFP responses (Ekas, Braungart-Rieker, Lickenbrock, Zentall, & Maxwell, 2011; Planalp, Braungart-Rieker, Lickenbrock, & Zentall, S. (in press). For the purposes of this study, data from all but the last visit were examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When infants are denied access to an attractive toy as well as responses from the mother, they may experience frustration. Research has shown that certain regulatory behaviors are more adaptive than others in reducing frustration (Stifter & Braungart, 1995; Buss & Goldsmith, 1998; Diener & Mangelsdorf, 1999; Ekas, Braungart-Rieker, Lickenbrock, Zentall, & Maxwell, 2011); thus, it may be most adaptive to orient towards the toy and the mother at first, but turn to other strategies, such as redirecting attention towards the environment, that will help reduce frustration when the mother continues to be unresponsive. In addition, strategies such as avoidance (e.g., pushing back on the high chair in which they are seated) or tension reduction behaviors (e.g., actively banging legs against the high chair) may be less adaptive in that they either maintain or increase infants’ frustration.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative conceptualization of distraction is that it represented active attempts at emotion regulation by participants. Such selfdistraction has been identified as a strategy, which whilst commonly shown by typical children, varies greatly across individuals in its efficacy for reducing negative emotions (Buss & Goldsmith, 1998;Ekas et al 2011). Thus, one interesting possibility is that the present participants (to differing degrees) engaged in, but were not able to successfully manage their negative emotions using, a self-distraction strategy.…”
Section: Discussionmentioning
confidence: 87%